2005
DOI: 10.1007/s00436-005-0020-z
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of NADH→NADP+ transhydrogenation by adult Hymenolepis diminuta mitochondria

Abstract: Hymenolepis diminuta mitochondria catalyze nonenergy-linked and energy-linked NADH-->NADP(+) transhydrogenations, with the latter driven by electron-transport dependent NADH oxidation (electron transport-driven, ETD) or ATP hydrolysis (ATP-driven, ATPD). Using submitochondrial particles, NADH-->NADP(+) transhydrogenations were characterized further. ETD and ATPD reactions were enhanced by bovine serum albumin (BSA) and were inhibited by N,N'-dicyclohexylcarbodiimide (DCCD), carbonyl cyanide 3-chlorophenylhydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
14
0
2
Order By: Relevance
“…Although niclosamide was proposed to kill parasitic helminths by uncoupling oxidative phosphorylation and disrupting NADH→NADP + transhydrogenation (28,29), we discovered that niclosamide causes a striking increase in ROS in human cancer cells, which at least partially contributes to the onset of apoptosis. We also showed that ROS elevation and NF-κB inactivation may be independent biological activities of niclosamide.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although niclosamide was proposed to kill parasitic helminths by uncoupling oxidative phosphorylation and disrupting NADH→NADP + transhydrogenation (28,29), we discovered that niclosamide causes a striking increase in ROS in human cancer cells, which at least partially contributes to the onset of apoptosis. We also showed that ROS elevation and NF-κB inactivation may be independent biological activities of niclosamide.…”
Section: Discussionmentioning
confidence: 90%
“…Niclosamide was reported to inhibit the NADH→NADP + transhydrogenation on Hymenolepis diminuta submitochondrial particle assay (28,29). We therefore assessed whether niclosamide induced intracellular ROS generation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Niclosamide functions to inhibit NADH→NADP+ transhydrogenation driven by electron transport-dependent NADH oxidation and increases ROS level (18). Excessive ROS disrupts the mitochondrial permeability transition that is an important step for the induction of mitochondria-mediated cell death.…”
Section: Niclosamide Induces Mitochondrial Dysfunctions In Hela Cellsmentioning
confidence: 99%
“…В России известен под названием фенасал [1]. Показано, что никлозамид является разобщителем дыхания и окислительного фосфорилирования в митохондриях ленточных гельминтов [2], улиток [3] и опухолевых клеток [4].…”
Section: никлозамидunclassified